Feeding Value of Some Cassava By-Products Meal for Poultry: A Review - Diarra, S.S.; Devi, A. (Pakistan Journal of Nutrition, 2015)
Cassava root meal which has been used as good alternative energy source in poultry and pig diets is increasingly becoming an important energy source for feeding the world’s human population. There are however, several by-products of cassava harvest ranging from the leaves, peels and pulp which have potential as feed ingredients in poultry rations. Cassava peels and pulps are moderate to high in energy and have been included in diets as replacements for conventional energy sources. Cassava leaves, moderate to good protein contents, have been used as protein supplements. Dietary recommendations of cassava by-products for poultry have varied considerably. The major factors limiting the efficient utilization of these by-products in poultry diets include the high fibre and low energy contents and likely presence of antinutritional factors, mainly hydrocyanic acid (HCN) in the bitter variety of cassava. Several technologies have been used to improve the utilization of cassava by-products by poultry. The following paper reviewed the composition of some cassava by-products (leaves, peels and pulp), their recommendations for inclusion in poultry diets and processing methods to maximize their utilization by poultry. It was concluded that efficient use of cassava by-products will reduce feed cost of poultry production and provide additional source of income to cassava farmers and processors.